Sphingolipids Contribute to Human Atherosclerotic Plaque Inflammation - Edsfeldt, Andreas; Dunér, Pontus; Ståhlman, Marcus; Mollet, Ines G.; Asciutto, Giuseppe; Grufman, Helena; Nitulescu, Mihaela; Persson, Ana Flor; Fisher, Rachel M.; Melander, Olle; Orho-Melander, Marju; Borén, Jan; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2016)
OBJECTIVE—Lipids are central to the development of atherosclerotic plaques. Specifically, which lipids are culprits remains controversial, and promising targets have failed in clinical studies. Sphingolipids are bioactive lipids present in atherosclerotic plaques, and they have been suggested to have both proatherogenic and antiatherogenic. However, the biological effects of these lipids remain unknown in the human atherosclerotic plaque. The aim of this study was to assess plaque levels of sphingolipids and investigate their potential association with and contribution to plaque vulnerability. APPROACH AND RESULTS—Glucosylceramide, lactosylceramide, ceramide, dihydroceramide, sphingomyelin, and sphingosine-1-phosphate were analyzed in homogenates from 200 human carotid plaques using mass spectrometry. Inflammatory activity was determined by analyzing plaque levels of cytokines and plaque histology. Caspase-3 was analyzed by ELISA technique. Expression of regulatory enzymes was analyzed with RNA sequencing. Human coronary artery smooth muscle cells were used to analyze the potential role of the 6 sphingolipids as inducers of plaque inflammation and cellular apoptosis in vitro. All sphingolipids were increased in plaques associated with symptoms and correlated with inflammatory cytokines. All sphingolipids, except sphingosine-1-phosphate, also correlated with histological markers of plaque instability. Lactosylceramide, ceramide, sphingomyelin, and sphingosine-1-phosphate correlated with caspase-3 activity. In vitro experiments revealed that glucosylceramide, lactosylceramide, and ceramide induced cellular apoptosis. All analyzed sphingolipids induced an inflammatory response in human coronary artery smooth muscle cells. CONCLUSIONS—This study shows for the first time that sphingolipids and particularly glucosylceramide are associated with and are possible inducers of plaque inflammation and instability, pointing to sphingolipid metabolic pathways as possible novel therapeutic targets.